THE RELEVANCE, ACHIEVEMENTS AND CHALLENGES OF WOMEN'S PARTICIPATION IN STEM IN UZBEKISTAN ANALYSIS AND CONCLUSIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article analyzes the importance of women's active participation in science and technology, especially in STEM (Science, Technology, Engineering, and Mathematics), the state policies and initiatives being implemented in this regard, the achievements and challenges in ensuring gender equality in each area, as well as the impact of women's participation in science on the socio-economic development of society.